Penerapan Program SAKRAL Untuk Meningkatkan Kompetensi Guru Dalam Pembuatan Media Pembelajaran Berbasis Digital di SMP Negeri 1 Tembuku - Pradnyana, I Putu Eka; Wisarja, I Ketut (Jayapangus Press, 2025)
Technology has a very important role in expanding access to information and learning opportunities. Many teachers at SMP Negeri 1 Tembuku face difficulties in adapting to the application of technology in the learning process, therefore new strategies are needed to improve teachers in increasing their ability to use technology in the learning process through training in creating digital-based learning media through the SAKRAL program. The aim of this research is to determine the influence of the SAKRAL program on the competence of teachers in making digital-based learning media at SMP Negeri 1 Tembuku. The method used is descriptive quantitative where data is obtained through the distribution of instruments to respondents who are then analyzed descriptively. The results of the research show that the average use and mastery of teachers in making digital-based learning media has increased in the category of very good by 10%, Good by 40%, Sufficient by 3.33%. And experienced a decrease in the Less category by 46.27%, and Very Less by 16.67%. Average student satisfaction and understanding of the material explained by the teacher by using digital-based learning media experienced an increase in the very good category by 26.47%, Good by 58.82%. As for the Sufficient category experienced a decrease of 32.35%, the Low category by 52.94%, and Very Low by 0%. The improvement of school performance in the digital field experienced an increase of 18 performances in a year from 2022 since the beginning of the implementation of the SAKRAL program until 2023. From the data it can be categorized that the application of the SAKRAL program can increase the competence of teachers in the use and creation of digital-based learning media, improving student understanding related to the material being learned and increasing student motivation in following learning as well as improving school performance in the field of digitization.